Place branding practice and scholarship: where we are and whither we may be going - Govers, Robert (Edward Elgar Publishing, 2021)
2020 has clearly been the year in which most people on this planet, most organisations, most economic sectors, most government agencies, had to reassess their priorities. Who and what contributes most to life; the economy; society? This opinion piece ponders the question of how place branding will be judged and where it might go in the coming years.